Inclusive Mathematics Education: State-of-the-Art Research from Brazil and Germany - Kollosche, David; Marcone, Renato; Knigge, Michel; Penteado, Miriam Godoy [UNESP]; Skovsmose, Ole [UNESP] (Springer Nature, 2019)
The book provides an overview of state-of-the-art research from Brazil and Germany in the field of inclusive mathematics education. Originated from a research cooperation between two countries where inclusive education in mathematics has been a major challenge, this volume seeks to make recent research findings available to the international community of mathematics teachers and researchers. In the book, the authors cover a wide variety of special needs that learners of mathematics may have in inclusive settings. They present theoretical frameworks and methodological approaches for research and practice.
Keywords: Autism; Auto-exclusion; Brazilian sign language; Cerebral palsy; Deaf education; Deficiencialism; Digital technologies; Heterogeneity in mathematics education; Language and mathematics; Learning environments; Learning processes; Macroinclusion; Mathematical literacy; Mathematics education; Maths anxiety; Microinclusion; Response to intervention framework; School inclusion; Special education; Teacher softskills